NUTRITIONAL CONTENT AND A PHASE - I SAFETY CLINICAL TRIAL OF A HERBAL-NUTRITIONAL SUPPLEMENT (IMUNITI) WITH PUTATIVE IMMUNE-MODULATING PROPERTIES - Matsabisa, M G; Sekhoacha, M P; Ibrahim, O; Moodley, P; Faber, M (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The relationship between HIV and AIDS and poor nutrition has been well established. Poor nutrition hastens the progression of HIV infection to AIDS. The rising pandemic of HIV and AIDS and high toxicity associated with anti-retroviral use are major factors that have compelled research to explore traditional herbal medicines as potential alternatives or supplements to anti-retroviral agents. A Phase I clinical trial was conducted on IMUNITI Wellness Pack, a herbal product with putative immune-modulating properties. The product is a combination of 7 herbal preparations, minerals, vitamins, and a specially formulated soya-maize meal porridge and a bottle of water purifier. The aim was to evaluate the safety and tolerability of IMUNITI, with a purpose of developing it for use in HIV-infected patients. The phase I study was conducted at the MRC clinic in Botha’s hill and the study lasted 5 weeks from date of participant dosing. The study was a randomised blinded placebo-controlled phase I clinical trial conducted on 48 healthy males. The participants were randomly divided into 4 groups of 12. The 3 groups received different escalating doses of IMUNITI while the forth group received placebo tablets. Participants consumed IMUNITI daily for a period of 5 weeks. Assessments were done at baseline, week 1 and week 5 to determine the safety parameters in all participants. In this study, IMUNITI did not show any safety concerns. In all study participants, there were no significant changes above the upper limit of the reference ranges of the laboratory tests for full blood count, INR, renal and biochemical safety parameters. IMUNITI was well tolerated. Furthermore, the nutritional content analysis of IMUNITI showed that it is a high kilojoule, high protein content product which contains a mixture of sugars, vitamins, traces of calcium, phosphorus and minerals.